Content Validation of Clinician-Reported Items for a Severity Measure for CDKL5 Deficiency Disorder. (October 2021) - Saldaris, Jacinta; Weisenberg, Judith; Pestana-Knight, Elia; Marsh, Eric D.; Suter, Bernhard; Rajaraman, Rajsekar; Heidary, Gena; Olson, Heather E.; Devinsky, Orrin; Price, Dana; Jacoby, Peter; Leonard, Helen; et al.
CDKL5 deficiency disorder (CDD) results in early-onset seizures and severe developmental impairments. A CDD clinical severity assessment (CCSA) was previously developed with clinician and parent-report items to capture information on a range of domains. Consistent with US Food and Drug Administration (FDA) guidelines, content validation is the first step in evaluating the psychometric properties of an outcome measure. The aim of this study was to validate the content of the clinician-reported items in the CCSA (CCSA-Clinician). Eight neurologists leading the USA CDD Center of Excellence clinics were interviewed using the "think aloud" technique to critique 26 clinician-reported items. Common themes were aggregated, and a literature search of related assessments informed item modifications. The clinicians then participated in 2 consensus meetings to review themes and finalize the items. A consensus was achieved for the content of the CCSA-Clinician. Eight of the original items were omitted, 11 items were added, and the remaining 18 items were revised. The final 29 items were classified into 2 domains: functioning and neurologic impairments. This study enabled refinement of the CCSA-Clinician and provided evidence for its content validity. This preliminary validation is essential before field testing and further validation, in order to advance the instrument toward clinical trial readiness.